2000
DOI: 10.1038/sj.jea.7500068
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of annual external radiation doses at values near minimum detection levels of dosimeters at the Hanford nuclear facility

Abstract: In epidemiological studies of workers exposed to ionizing radiation, recognition of the limitations of available radiation dosimetry data is important to interpretation of a study's findings. This paper provides an investigation of external radiation dosimetry data for workers at the Hanford nuclear facility, focusing on changes over time in practices for recording dosimetry measurements that were between zero and the minimum detectable level of a radiation dosimeter. Reported annual external radiation doses f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The primary occupational exposure under investigation at Hanford has been external penetrating ionizing radiation. These external exposures have been routinely quantified using personal dosimeters for a majority of workers included in epidemiologic studies [Gilbert, 1990;Kneale et al, 1991;Gilbert and Fix, 1996;Richardson et al, 1999Richardson et al, , 2000. Epidemiologic studies have demonstrated dose-response relationships for cancer mortality and external radiation exposures at older ages [Stewart and Kneale, 1989Stewart, 1993, 1995], but not for cumulative exposures across all ages [Gilbert et al, 1989[Gilbert et al, , 1993a.…”
Section: Introductionmentioning
confidence: 99%
“…The primary occupational exposure under investigation at Hanford has been external penetrating ionizing radiation. These external exposures have been routinely quantified using personal dosimeters for a majority of workers included in epidemiologic studies [Gilbert, 1990;Kneale et al, 1991;Gilbert and Fix, 1996;Richardson et al, 1999Richardson et al, , 2000. Epidemiologic studies have demonstrated dose-response relationships for cancer mortality and external radiation exposures at older ages [Stewart and Kneale, 1989Stewart, 1993, 1995], but not for cumulative exposures across all ages [Gilbert et al, 1989[Gilbert et al, , 1993a.…”
Section: Introductionmentioning
confidence: 99%
“…The recording thresholds employed at SRS were relatively low when contrasted with the thresholds used at other USDOE sites at comparable periods and there is evidence of a high-level of consistency over time in SRS dosimetry recording practices (Wing et al, 1994;Richardson et al, 2000). Identifying employment-years with missing annual external dosimetry information is an important step in the assessment of potential exposure misclassification bias.…”
Section: Resultsmentioning
confidence: 99%
“…As these analyses examine annual external dosimetry data (which are the sum of more frequent periodic dosimetry measurements) the findings 1951 1952 1953 1954 1955 1956 1957 1958 1959 1960 1961 1962 1963 1964 1965 1966 1967 1968 1969 1970 1971 1972 1973 1974 1975 1976 1977 1978 1979 1980 1981 1982 1983 1984 1985 1986 1987 1988 1989 UNC/NIOSH review of historical logbooks provide indirect evidence about recording practices. However, as illustrated in prior studies (Wing et al, 1994;Richardson et al, 2000), useful inferences can be drawn about recording practices from analyses of annual dosimetry data.…”
Section: Evaluation Of Recording Thresholdsmentioning
confidence: 99%